Cyber security for smart inverters and distributed energy resources (DER) - Khayoon, Qaeser Mohsen; Al-Fatlawi, Hassan Hadi M. A.; Albhadly, Ali Jasim (Al-Nahrain Journal for Engineering Sciences, 2026)
The growing use of “distributed energy resources (DER)” will result in a significant increase in the total number of gadgets or devices that users and third parties own and control. These gadgets rely largely on digital communication and control, placing them in danger due to cyber threats. This study presents a comprehensive framework that is resistant to attacks for defending integrated DER and major power grid infrastructure from hostile cyber-attacks, ensuring the safe integration of DER without jeopardizing system dependability and stability. This research focuses on the development of a cyber-physical power system that incorporates a significant integration of DER and analyses the particular cyber security problems brought about by DER integration. Following that, we provide a systematic DER resilience analysis approach, in addition to effective and measurable resilience measurements and concepts concerning design, and we summarize important DER assault scenarios. In conclusion, we suggest preventive, detective, and responsive measures against cyber-attacks, specifically tailored for integrating Distributed Energy Resources (DER) throughout the physical, cyber device, and regulatory levels of an eventual smart grid.